Practical considerations for data exploration in quantitative cell biology - Pylvänäinen, Joanna W.; Grobe, Hanna; Jacquemet, Guillaume (The Company of Biologists, 2025)
Data exploration is an essential step in quantitative cell biology, bridging raw data and scientific insights. Unlike polished, published approach that reveals trends, identifies outliers and refines hypotheses. This Opinion offers simple, practical advice for building a structured data exploration workflow, drawing on the authors' personal experience in analyzing bioimage datasets. In addition, the increasing availability of generative artificial intelligence and large language models makes coding and improving data workflows easier than ever before. By embracing these practices, researchers can streamline their workflows, produce more reliable conclusions and foster a collaborative, transparent approach to data analysis in cell biology.